2009
DOI: 10.1088/0022-3727/42/6/065401
|View full text |Cite
|
Sign up to set email alerts
|

Localized deformation of a Cu46.25Zr45.25Al7.5Er1bulk metallic glass

Abstract: Using the cavity model and the concept of the plastic-hardening modulus, a simple relationship was established between the size of an indent and the size of a semi-spherical-shell softening zone. Indentation experiments of a Cu46.25Zr45.25Al7.5Er1 bulk-metallic glass (BMG) were performed over a range of indentation loads from 500 to 4000 mN, using a Vickers indenter. The indentation hardness decreased slightly with the increase in the indentation load from 5.21 GPa at an indentation load of 500 mN to 4.66 GPa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…It should be noted that the values of U pl /U tot shown in Fig. 4(b) are in agreement with those reported for Zr 50 Cu 40 Al 10 (U pl /U tot ∼ 0.6 [27]) and Cu 46.25 Zr 45.25 Al 7.5 Er 1 BMG (U pl /U tot ∼ 0.7 [28]) and clearly larger than for brittle Fe-based BMG (U pl /U tot ∼ 0.37 [19]). In fact, the ratio U pl /U tot has been sometimes used to characterize the mechanical behavior of brittle materials which are often difficult to test using macroscopic tensile tests [29].…”
Section: Resultssupporting
confidence: 90%
“…It should be noted that the values of U pl /U tot shown in Fig. 4(b) are in agreement with those reported for Zr 50 Cu 40 Al 10 (U pl /U tot ∼ 0.6 [27]) and Cu 46.25 Zr 45.25 Al 7.5 Er 1 BMG (U pl /U tot ∼ 0.7 [28]) and clearly larger than for brittle Fe-based BMG (U pl /U tot ∼ 0.37 [19]). In fact, the ratio U pl /U tot has been sometimes used to characterize the mechanical behavior of brittle materials which are often difficult to test using macroscopic tensile tests [29].…”
Section: Resultssupporting
confidence: 90%
“…It can be seen from Figure 7b that the plasticity index U p /U t increases gradually with increasing α-Fe phase. The values of U p /U t with different α-Fe phases are above 0.8, which is close to the Ti 40 Zr 10 Cu 38 Pd 12 [27] and Cu 46.25 Zr 45.25 Al 7.5 Er 1 [31] BMGs, indicating that the printed Fe-based BMGs have intrinsic plasticity thanks to the existence of α-Fe phase.…”
Section: Mechanical Propertiessupporting
confidence: 62%
“…In the previous indentation studies of BMGs, the experimental revelation of the subsurface shear-band structures has been attempted using different approaches, 12,14,18,34,35 which entails the Vickers indentation on a bonded interface 14 plate. 12,18,34 Based on the experimental results, it was found that the pattern of the shear bands exposed on the surface of observation generally matched the predictions of the continuum theories well at the macroscopic scale.…”
Section: Subsurface Shear-band Patterns At the Submicron Scalementioning
confidence: 99%